Biological Activities and Cell Proliferation effects of Red Ginseng Ethanol Extracts - Sung-Yeoun Hwang; Seong-Hun Ahn (Journal of Pharmacopuncture, 2011)
Objectives: Reactive Oxygen Species(ROS) are continuously produced at a high rate as a by-product of aerobic metabolism. Since tissue damage by free radical, ROS such as hydrogen peroxide(H2O2), nitric oxide(NO) increases with age. Several lines of evidence provided that ROS appears to cause to develop aging-related various diseases such as cancer, arthritis, cardiovascular disease. In this study, we have conducted to investigate the pharmacological effects of red ginseng for the development possibility to pharmacopuncture drug sources or healthy aid foods. Methods: For our aims, it was investigated the biological activities of Red Ginseng ethanol extracts (RGEE) by measuring total polyphenol contents, total flavonoid contents, DPPH radical scavenging activity, ABTS radical scavenging activity and cell viability of MCF 10A and SK-MEL-2 in vitro with MTT assay method. Results: The total polyphenol contents of RGEE was 3.06􀅾0.11mg/g in 10mg/ml, the total flavonoid contents of RGEE was 1.35􀅾0.01mg/g in same concentration. The ABTS radical scavenging activity was about 80% and that of DPPH activity was 65% in 50mg/ml of RGEE. The cell viability of SKMEL-2, skin cancer cell line was decreased and that of MCF 10A, skin normal cell line was increased. Conclusions: We conclude that RGEE may be useful as potential functional foods or pharmacopuncture drug sources on the diseases induced by oxidant stress.